Chalcogenide perovskites for photovoltaics: current status and prospects. (12th May 2021) - Tiwari, Devendra; Hutter, Oliver S; Longo, Giulia
Abstract: Chalcogenide perovskite materials are anticipated to have favourable structural, optical and electronic characteristics for solar energy conversion, yet experimental verification of the numerous computational studies is still lacking. In this perspective we summarise and critically review the computational and synthetic achievements, whilst suggesting new pathways for achieving the goal of developing this exiting class of materials. Greater knowledge of phase chemistry would allow the realisation of bandgap engineering through mixed cation and anion compositions. Combining this with fabrication and characterisation of thin films could yield promising new tailored materials for photovoltaic absorbers in the near future.